Cells with loss-of-heterozygosity after exposure to ionizing radiation in Drosophila are culled by p53-dependent and p53-independent mechanisms - Brown, Jeremy (PLoS Genet, 2020)
Loss of Heterozygosity (LOH) typically refers to a phenomenon in which diploid cells that are heterozygous for a mutant allele lose their wild type allele through mutations. LOH is implicated in oncogenesis when it affects the remaining wild type copy of a tumor suppressor. Drosophila has been a useful model to identify genes that regulate the incidence of LOH, but most of these studies use adult phenotypic markers such as multiple wing hair (mwh). Here, we describe a cell-autonomous fluorescence-based system that relies on the QF/QS transcriptional module to detect LOH, which may be used in larval, pupal and adult stages and in conjunction with the GAL4/UAS system. Using the QF/QS system, we were able to detect the induction of cells with LOH by X-rays in a dose-dependent manner in the larval wing discs, and to monitor their fate through subsequent development in pupa and adult stages. We tested the genetic requirement for changes in LOH, using both classical mutants and GAL4/UAS-mediated RNAi. Our results identify two distinct culling phases that eliminate cells with LOH, one in late larval stages and another in the pupa. The two culling phases are genetically separable, showing differential requirement for pro-apoptotic genes of the H99 locus and transcription factor Srp. A direct comparison of mwh LOH and QF/QS LOH suggests that cells with different LOH events are distinguished from each other in a p53-dependent manner and are retained to different degrees in the final adult structure. These studies reveal previously unknown mechanisms for the elimination of cells with chromosome aberrations.